Invisible criticism : Ralph Ellison and the American canon - Nadel, Alan, 1947- (University of Iowa Press, 1988)
In 1952 Ralph Ellison won the National Book Award for his Kafkaesque and claustrophobic novel about the life of a nameless young black man in New York City. Although Invisible Man has remained the only novel that Ellison published in his lifetime, it is generally regarded as one of the most important works of fiction in our century.